G13 Timely completion of discharge letters in a busy paediatric assessment unit (PAU): A challenge overcomed. (24th May 2017) - Verma, P; Saleem, Z; Vantra, A; Ladak, B; Bhaduri, A
Abstract : Background: Patient discharge documentation in PAU was not always completed within 48 hours of discharge. This was felt to be poor practice and potential risk to patient safety. A QIP ( Quality Improvement Project) was formulated with 'champions' identified from senior and junior medical staff in collaboration with nursing and managerial input. Methods: After initial assessment of the backlog, a pilot for 6 weeks was designed using the PDSA model (Plan Do Study Act) with targeted and specific outcomes. Weekly team meetings were held for planning and disseminating the structured approach. A no compromise policy to finish prospectively all discharge summaries was adopted. A closed communication group for real time daily update of progress was set up. Nursing and admin staff were encouraged to bring the notes of pending summaries to the morning handover to delegate the work load between medical staff of all grades. Outcome data on the time and causes of delay in completion of discharge letters was collected through a data capture form filled in by doctors and nurses. Data was analysed and results were fed back to all staff weekly at grand rounds for 6 weeks. Results: Timely completion of discharge summaries improved significantly (48% at Week 2 compared with 100% at Week 6) with the entire backlog fully completed by the end of pilot. Conclusion: Becoming the change agent helped changing behaviour of others. This is a perfect example of bottoms up approach with a focus for solution and engagement of the staff on the shop floor. The PDSA model, staff ownership of the project and striking a balance between a proactive need to finish the summaries as well as a reactive approach in identifying and implementing feasible solutions by the champions helped not only with the success of the project but also contributed to changing the culture of the entire team. Improvement is being sustained by ensuring champions are identified from each cohort of junior doctors and daily updates from hospital informatics regarding pending discharge letters.